Study on pathological and clinical characteristics of chronic HBV infected patients with HBsAg positive, HBV DNA negative, HBeAg negative - Zeng, Zhan; Liu, Ruyu; Cao, Weihua; Yang, Liu; Lin, Yanjie; Bi, Xiaoyue; Jiang, Tingting; Deng, Wen; Wang, Shiyu; Lu, Huihui; Sun, Fangfang; Shen, Ge; et al. (Frontiers in Immunology, 2023)
Aims Study of clinical characteristics of hepatitis B virus deoxyribonucleic acid (HBV DNA)-negative, hepatitis B surface antigen (HBsAg)-positive, hepatitis B e antigen (HBeAg)-negative patients based on liver histopathology. Methods We retrospectively enrolled patients with chronic HBV infection diagnosis at Beijing Ditan Hospital from May 2008 to November 2020. To study the differences between patients with significant hepatic histopathology and those without significant hepatic histopathology. And to study the independent factors of significant hepatic histopathology. Results 85 HBV DNA-negative and HBeAg-negative patients were 37.90 ± 10.30 years old, 23.50% of patients with grade of inflammation (G) >1, 35.30% of patients with liver fibrosis stage (S) >1, 44.70% patients were diagnosed with significant hepatic histopathology. Compared to the no significant hepatic histopathology group, another group had older age (41.70 ± 10.70 vs 34.80 ± 8.87 years, t=-3.28, P=0.002), higher total bilirubin (TBIL) [14.9(10.3, 22.4) vs 11(8.9, 14.4) μmol/L, z=-2.26, P=0.024], lower cholinesterase (CHE) (t=-2.86, P=0.005, 7388.00 ± 2156.00 vs 8988.00 ± 2823.00 U/L) and lower platelet (PLT) (t=2.75, P=0.007, 157.00 ± 61.40 vs 194.00 ± 61.00 10^9/L). Abnormal ALT patients are more likely to have significant hepatic histopathology (z=5.44, P=0.020, 66.70% vs 337.50%). G had significant correlation with CHE (P=0.008, r=-0.23), alanine aminotransferase (ALT) (P=0.041, r=0.18), aspartate aminotransferase (AST) (P=0.001, r=0.29). S had significant correlation with TBIL (P = 0.008, r = 0.23), age (P < 0.001, r = 0.32), international normalized ratio (INR) (P = 0.04, r = 0.23), CHE (P < 0.001, r = -0.30), PLT (P < 0.001, r = -0.40) and prothrombin time activity (PTA) (P = 0.046, r = -0.22). Multivariate logistic analysis indicated only age (95%CI=1.014~1.130, OR=1.069, P=0.013) was an impact factor for significant hepatic histopathology. The cutoff point of age was 34.30 years. Conclusions A large proportion of chronic HBV infection patients with HBeAg-negative and HBV DNA-negative still have chronic hepatitis. Age is an independent factor for significant hepatic histopathology